Characterization of accumulated unknown and soil dust on the PV system: An experimental study on the impact and performance analysis - Islam, Md. Imamul; Mohd Shawal, Jadin; Al Mansur, Ahmed (Elsevier, 2025)
Dust accumulation on PV module surfaces directly impacts incident solar radiation, resulting in a significant decrease in the electrical performance of large-scale solar power plants. In this investigation, the characterization and impact of unknown and soil dust particles on PV systems at the Pasir Mas Solar Farm in Kelantan, Malaysia, were examined. The principal goal was to comprehend the impact of accumulated dust on the performance of PV systems and to characterize the dust samples. Using state-of-the-art lab facilities, the investigation disclosed the physical, optical, morphological, and chemical characteristics of both known and unknown dust. The impact of deposited dust was also identified using thermal imaging techniques and I–V data measurements. The results of the particle size analysis indicated a Z-average size of 4730 nm and a Polydispersity Index of 1.0. The SEM and EDS analyses revealed heterogeneous particle sizes with substantial quantities of SiO2 and Al2O3. The UV–VIS–NIR spectroscopy found a high absorbance characteristic of the dust which may result in thermal degradation. According to I–V data measurements, only 0.88% and 41.60% of the 226 strings met the expected Voc and Isc, respectively, and thermal imaging detected that approximately 19.91% of the PV strings were affected by hotspots. However, the performance ratio of the plant ranged from 81% to 89%, with an average of 85.82%, and efficiency varied between 12% and 13%. The study concludes that PV performance is substantially influenced by dust, underscoring the necessity of efficient cleaning methods and proposing future research on chemical cleaning processes.